2005
DOI: 10.1345/aph.1e271
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Meropenem in Febrile Neutropenic Patients with Bacteremia

Abstract: To our knowledge, this is the first published report of a relationship between a pharmacodynamic index and clinical outcome in a febrile neutropenic population. Based on this relationship, dosing with intravenous meropenem 500 mg every 6 hours is predicted to be comparable to the currently recommended 1 g every 8 hours for serious infections. Our model provides further justification for a prospective clinical trial to evaluate a pharmacodynamically targeted meropenem dosing schedule as to its ability to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 26 publications
7
131
1
4
Order By: Relevance
“…This is further supported by studies that correlate optimised antibiotic exposure with improved patient outcome [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is further supported by studies that correlate optimised antibiotic exposure with improved patient outcome [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 72%
“…A c c e p t e d M a n u s c r i p t 8 Confirmation of dosing appropriateness through monitoring of plasma concentrations is therefore essential for -lactam antibiotics in the critically ill patient population. Routine therapeutic drug monitoring (TDM), enables a rational, patient specific dose adjustment thereby maximizing treatment efficacy while minimizing drug toxicity [35].…”
Section: Page 8 Of 48mentioning
confidence: 99%
“…However, as also observed in the studies described above (11,13), treatment failure with rapid resistance emergence nonetheless occurred even in some situations where fT ϾMIC was at or close to 100%. Such in vitro findings plus data from recent retrospective clinical studies supporting a longer fT ϾMIC in critically ill patients (42)(43)(44)(45) challenge the traditional PK/PD targets. With maximal bactericidal activity of the ␤-lactams occurring at 4ϫ to 5ϫ MIC (46,47) and regrowth often observed as soon as concentrations fall below the MIC (48-50), other targets, e.g., 100% fT Ͼ4 -5ϫMIC (14, 51, 52) and fC min /MIC, have been investigated.…”
Section: Effect Of Meropenem Clearance On Antibacterial Effectsmentioning
confidence: 98%
“…Therefore population pharmacokinetic parameters are essential for Monte Carlo simulation. Population pharmacokinetic analyses have been generally determined in healthy volunteers, since several studies have indicated that there is no difference between healthy volunteers and patients in terms of pharmacokinetic profiles [17,19]. Nevertheless, true between-patient variability was observed in our patients.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 88%